Neuroaxial anesthesia in a patient with progressive systemic sclerosis : case presentation and review of the literature on systemic sclerosis - Erk, Gülcan (BioMed Central, 2006)
BACKGROUND: Systemic sclerosis (SSc), a progressive disease characterized by excessive accumulation of connective tissue components. Although most patients have long survival, some of them progress rapidly to death. Pulmonary system involvement and pulmonary hypertension are the most frequent cause of death. When the patient with SSc is to be operated, the anesthetic procedure could be a serious problem. In this article, we report a combined spinal – epidural technique in a patient with progressive SSc and the anesthetic considerations that could be recommended for these patients. CASE PRESENTATION: A 68-year-old woman who had a history of progressive systemic sclerosis, pulmonary fibrosis, kyphoscoliosis and decreased oral apertura underwent total hip arthroplasty. This operation was performed successfully under combined spinal epidural anesthesia. CONCLUSION: Systemic sclerosis is a complex disease that involves multiple organ systems. Every aspects of anesthetic care may be altered or hindered by the pathogenesis of disease. Although the choice of regional or general anesthesia is unclear, to choose combined spinal epidural anesthesia may be useful.